An Analysis on Politeness of Non-Verbal Communication in an English as a Foreign Language Classroom - Imanuel Kamlasi; Anselmus Sahan (Universitas Hamzanwadi, 2022)
In an EFL classroom; teachers tend to use politeness of non-verbal communication to convey meaning(s) to students. This present research aims at analyzing and describing the politeness of non-verbal communication which was used by English teachers in EFL classrooms. Qualitative research was applied in this research. There were five English teachers chosen purposely as the participants. The data were the pictures of teachers’ gestures. To obtain the data, the researchers used a Tape Video Recorder (TVR) which was used to record the teachers’ gestures during the teaching and learning process. The researchers applied transcription, codification, classification, analyses, and discussion techniques to analyze data. The results showed that there were 16 politeness strategies used by the English teachers in the EFL classroom. Those politeness strategies are greetings, thanking, congratulating/praising, and apologizing, obedience, intimacy, joke, rejection, question/ evaluating, request, suggestion, chastisement, disagreement, asking permission, optimism, and instructing. The politeness of non-verbal communication has a positive impact on students in EFL classroom interaction. In some cases, the students found it difficult to understand the meanings of gestures.